An imazamox-based herbicide causes apoptotic changes in rat liver and pancreas. (2019) - Sevim, Çiğdem; Çomaklı, Selim; Taghizadehghalehjoughi, Ali; Özkaraca, Mustafa; Mesnage, Robin; Kovatsi, Leda; Burykina, Tatyana I.; Kalogeraki, Alexandra; Antoniou, Michael N.; Tsatsakis, Aristidis
Graphical abstract: Highlights: Toxicity of an imazamox-based herbicide was evaluated in rats. Blood samples were collected and serum ALP, AST, glucose, calcium and creatinine levels were determined. Imazamox formulation induced an increase in serum glucose and calcium. Liver and pancreatic tissue were studied by immunohistochemistry and in-situ hybridization. Necrotic and degenerative changes were observed in insulin positive ß cells. Abstract: We studied the acute toxicity of an imazamox-based herbicide at 12, 24 and 36 mg/kg body (bw) weight imazamox equivalent dose on the liver and pancreatic tissue in Sprague Dawley rats. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities, glucose, calcium as well as creatinine, were determined in blood samples, which were collected after 24, 48 and 72 h exposure. Caspase 3 and anti-insulin expression and immunopositivity were evaluated using in situ hybridization and immunohistochemistry, respectively. The imazamox-based herbicide evaluated in this study induced toxic effects even from the lowest dose tested (12 mg/kg bw). The two highest doses caused a statistically significant cytotoxicity on the Langerhans islet cells. Necrotic and degenerative changes were detected in hepatocytes at the two highest doses. Imazamox is considered to be poorly toxic to the liver. Nevertheless, the imazamox-based herbicide formulation tested here reduced the size of the β-islet cells, induced an elevation in serum glucose and calcium. Our data shows that commercial formulations of imazamox containing various co-formulants can have hepatic and pancreatic toxic effects.